The economics of ideas and intellectual property - Boldrin, Michele (National Academy of Sciences, 2005)
Innovation and the adoption of new ideas is fundamental to economic progress. Here we examine the underlying economics of the market for ideas. From a positive perspective, we examine how such markets function with and without government intervention. From a normative perspective, we examine the pitfalls of existing institutions, and how they might be improved. We highlight recent research by us and others challenging the notion that government awards of monopoly through patents and copyright are “the way” to provide appropriate incentives for innovation.